Development of Natural Plant Module Approach Around as a Learning Resource in UIN Walisongo Semarang - Zubail, Dien Rosiana; Retnoningsih, Amin; Ngabekti, Sri (Postgraduate, Universitas Negeri Semarang, Indonesia, 2018)
The management of natural resources (medicinal plants) is a material taught in the UIN Walisongo biology education department. Based on preliminary observations students experience saturation of learning in the classroom. Therefore, it is necessary to attempt to overcome this by using JAS approaching learning module. This study aims to: (1) identify the types of medicinal plants grown in Taman Jamu Nyonya Meneer (TJNM) and TOGA Park Patemon Tengaran Village; (2) developing JAS medicinal plant modules; (3) test the validity, practicality and effectiveness of the module. Characteristics of the module consists of concept maps, indicators, materials, tasks, quizzes, experiments and essay tests. This research is a research and development (R & D) which is designed consists of stages: (1) analysis of potentials and problems; (2) data collection; (3) product design of learning module; (4) module characteristics; (5) validation of product design; (6) revision of phase I module; (7) small scale module test; (8) revision of module stage 2; (9) final module revision. A limited-scale trial was conducted at UIN Walisongo. Data collection was done by observation method, interview, questionnaire, documentation and test. Trials were conducted to test the practicality and effectiveness of the module on students' cognitive, affective and psychomotor learning outcomes. The result of identification of medicinal plants in TJNM and TOGA Park Patemon Village was found by the number of medicinal plants in TJNM that is 49 species and in Patemon Tengaran Village that is 23 species. Validation results are valid by media experts and valid by material experts. The cognitive learning result of 84.67% of students reach completeness. Students and lecturers responded very well to the developed learning modules.